Integrating resilience attributes into local disaster management plans in Metro Manila: strengths, weaknesses, and gaps. (December 2022) - Ner, Nikko Torres; Okyere, Seth Asare; Abunyewah, Matthew; Kita, Michihiro
Abstract: Integrating resilience attributes into local plans is considered an important step in enhancing disaster risk reduction. However, the extent to which resilience is captured in local disaster management plans remains underexplored. This paper utilizes content analysis to examine the integration of the United Nations Office for Disaster Risk Reduction's (UNDRR) resilience attributes across 11 cities in Metro Manila. Results show strong integration in governance and risk identification while gaps exist in ecosystem protection, city-to-city learning, and disaster victims' participation in recovery planning. The paper recommends introducing metropolitan-level platforms for inter-city learning, turning local authorities' attention towards nature-based solutions, and including disaster victims in the recovery planning process. Highlights: The integration of resilience attributes is examined through content analysis. Governance and risk identification attributes are better integrated in DRR plans. Ecosystem protection remains a challenge in local DRR plans of Metro Manila cities. City-to-city learning is absent in the DRR plans of Metro Manila cities. Metropolitan coordination is integral to building disaster resilient planning.